Review of Oxidation of Gasoline Surrogates and Its Components - J. A. Piehl; A. Zyada; L. Bravo; O. Samimi-Abianeh (Journal of Combustion)
There has been considerable progress in the area of fuel surrogate development to emulate gasoline fuels’ oxidation properties. The current paper aims to review the relevant hydrocarbon group components used for the formulation of gasoline surrogates, review specific gasoline surrogates reported in the literature, outlining their utility and deficiencies, and identify the future research needs in the area of gasoline surrogates and kinetics model.